The Relationship Between Leg Muscle Strength, Arm Muscles and Confidence With 50 Meter Freestyle Swimming Speed - Johanna Matitaputty (Peneliti.net, 2023)
The purpose of this study was to find out the relationship between leg muscle strength and self-confidence, arm muscle strength and self-confidence, as well as leg muscle strength arm muscle strength and self-confidence with swimming speed 50 meters freestyle.The research sample consisted of 30 male students. In accordance with the formulation of the problem and the objectives to be achieved, the research method used in this study is a quantitative method with correlation and descriptive techniques, namely researchers will see the relationship between one variable and another. Based on the results of research data analysis and discussion, the results of the study can be concluded as follows (a) there is a relationship between leg muscle strength and swimming speed 50 meters freestyle of 3.61 (b) there is a relationship between arm muscle strength and swimming speed 50 meters freestyle of 3.47. (c) there is a relationship between self-confidence with a swimming speed of 50 meters freestyle of 4.95 with such a relationship between muscle strength of the limbs muscle strength of the arms and self-confidence with a swimming speed of 50 meters freestyle of 14.99.